Purine analogs as phosphatidylinositol 4-kinase IIIβ inhibitors - Šála, Michal; Kögler, Martin; Plačková, Pavla; Mejdrová, Ivana; Hřebabecký, Hubert; Procházková, Eliška; Strunin, Dmytro; Lee, Gary; Birkus, Gabriel; Weber, Jan; Mertlíková-Kaiserová, Helena; Nencka, Radim (Bioorganic & medicinal chemistry letters, 2016)
We report on an extensive structure-activity relationship study of novel PI4K IIIβ inhibitors. The purine derivative of the potent screening hit T-00127-HEV1 has served as a suitable starting point for a thorough investigation of positions 8 and 2. While position 8 of the purine scaffold can only bear a small substituent to maintain the inhibitory activity, position 2 is opened for extensive modification and can accommodate even substituted phenyl rings without the loss of PI4K IIIβ inhibitory activity. These empirical observations nicely correlate with the results of our docking study, which suggests that position 2 directs towards solution and can provide the necessary space for the interaction with remote residues of the enzyme, whereas the cavity around position 8 is strictly limited. The obtained compounds have also been subjected to antiviral screening against a panel of (+)ssRNA viruses.
Keywords: molekulární struktura; Hepatitis C virus; inhibitory proteinkinas; vztahy mezi strukturou a aktivitou; Antiviral Agents; Humans; antivirové látky; Protein Kinase Inhibitors; Rhinovirus; Enterovirus B, Human; PI4K IIIβ; Purines; Dose-Response Relationship, Drug; Antiviral agent; Models, Molecular; Microbial Sensitivity Tests; lidé; Phosphotransferases (Alcohol Group Acceptor); enterovirus B lidský; HeLa buňky; Phosphatidylinositol 4-kinase; vztah mezi dávkou a účinkem léčiva; puriny; mikrobiální testy citlivosti; molekulární modely; fosfotransferasy s alkoholovou skupinou jako akceptorem; Hepacivirus; Purine; HeLa Cells; Molecular Structure; Structure-Activity Relationship